Developing the j-QAF e-Learning Application for Children on Islam Obligatory Duties (Fardhu Ain) under the Topic 'Ibadat' - Azirawati Maziah, Aziz (2009)
Computer Aided Learning (CAL) has becomes the learning style at school and high institution. If before this, teachers used blackboard and text book, but nowadays teachers has been exposed with computer as an effective and interesting way. In Malaysia, utilization of computer was started in 1966, as long as it introduce,government try to apply it various field such as business, education, and life. Much effort has been done by government to increase the student skill in computer. In 1980’s, government was introduce computer club through the co curriculum activity at schools. In RMK-9, smart school project has been introduced by stages. It include three things, which is ICT hardware that supply to school, specific software and system application and also guidance for school admin, teacher, parent and community places. Learning through e-learning has been used at whole school in Malaysia either through CD ROM or online e-learning. The objective of this research is to help children understand the “ibadat” topic via j-QAF e-learning application. j-QAF e-learning application is developed by using dual coding theory by Paivio 1986,working memory theory by Baddley 1992 and cognitive load theory by Chanddler & Sweller 1991. In fact of design, multimedia learning theory by Richard Mayer has been used to make sure design of e-learning can be understood by children. All the theory are related each other to develop the j-QAF e-learning application. Dual coding theory explain that human brain in analyst information used two ways which is human’s process information through dual channels, one auditory and the other visual. So based on this theory, researcher has been developed e-learning with included two elements which is visual and verbal (auditory). It because according working memory theory human brain can actively process during learning process.But human brain can’t accept all the information that has been presented. So cognitive load theory has been used to assess that amount of information is limited to be process. Based on the three theories, so multimedia learning theory by Richard Mayer has been developed which is multimedia principle, spatial contiguity principle, temporal contiguity principle, Coherence Principle, Modality Principle,Redundancy Principle, and Individual Differences Principles which can balance the human brain. Evaluation session has been done at Sekolah Rendah Kebangsaan Kupang.